Analisis Produksi Gas Metana (CH4) Dan Karbon Dioksida (CO2) Dari Tempat Pembuangan Akhir Kota Pekanbaru - Herfi Rahmi; Aryo Sasmita; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In 2013, Municipal Solid Waste (MSW) of Pekanbaru was transported to landfill reach 14.631 tonnes/month from 999.031 people with 4,06% population growth rate. The waste in landfill will be decomposed in anaerobic digestion process and produced methane (CH4) with composition of 45%-60%. Based on Peraturan Menteri Pekerjaan Umum Republik Indonesia Nomor 03/Prt/M/2013 the operational of the landfill either by controlled landfill or sanitary landfill should be able to control the landfill gas, ensure the worker safety and emergency response and management of flammable threat. This research predicted the production and dispersion of methane gas and carbon dioxide from MSW of Pekanbaru landfill from anaerobic fermentation process. Production of methane gas and carbon dioxide were analyzed with LandGEM. Based on the LandGEM analysis shown that the total landfill gas from Pekanbaru landfill in 2020 will reach 3.147.585 m3/year equalsto 359,313 m3/hour. Total methane generation will reach 1.888.551 m3/year equals to 215,588 m3/hour and 1.259.034 m3/year equals to 143,725 m3/hour for total carbon dioxide.Keywords : production, dispersion, methane, carbon dioxide